HUBUNGAN STATUS EKONOMI ORANG TUA DAN PRESTASI BELAJAR OTOMOTIF DENGAN MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI SISWA KELAS XI PROGRAM KEAHLIAN TEKNIK OTOMOTIF SMK PERINDUSTRIAN YOGYAKARTA TAHUN PELAJARAN 2014/2015 - Taufik Winda Saputra; Pairun Roniwijaya (Jurnal Taman Vokasi, 2015)
The objectives of this study are to describe (1) correlation between parents’ social status with willing to continue their study in university level; (2) correlation between learning achievement of automotive subject with willing to continue their study in university level; and (3) correlation between parents’ social status and learning achievement of automotive subject with willing to continue their study in university level. This study was ex-post facto. Methods in collecting data used questioner and documentation. Techniques in analyzing the data used descriptive analysis, the first and second hypothesis used partial correlation and the third hypothesis used regression that was started by normality, linearity, and intercorrelation testing. This study shows that: (1) there was positive and significant correlation between parents’ social status with willing to continue their study in university level; (2) there was positif and significant correlation between learning achievement of automotive subject with willing to continue their study in university level; and (3) there was positive and significant correlation between parents’ social status and learning achievement of automotive subject with willing to continue their study in university level.